STRATEGI PENINGKATAN PERAN PEMERINTAH DAERAH DALAM PEMBIAYAAN PENDIDIKAN ANAK PAPUA - Edmundus Bawor; Prof. Dr. Masduki Ahmad, SH., MM. (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2023)
This article discusses strategies to increase the role of local governments in financing Papuan children's education. Local governments in Papua have a key responsibility in ensuring accessibility and good quality education for Papuan children but there are challenges in fulfilling this commitment such as limited financial resources and a lack of understanding of effective strategies. This article presents some strategies that can be implemented, including allocating a larger budget for education, improving coordination between relevant agencies, expanding scholarship programs, and improving the training and development of qualified teaching staff. By increasing the role of local governments in financing the education of Papuan children, it is hoped that the accessibility and quality of education for Papuan children will improve. In this article, research was conducted using a literature study approach. The steps used in literature study research include identification of research objectives, identification of literature sources, literature selection, literature evaluation, literature analysis, synthesis, and report writing. The role of the Papuan local government in financing education is very important to improve the quality of education of Papuan children and minimize educational disparities. Local governments work together with the central government, educational institutions, communities and the private sector to achieve this goal.